Escherichia coli Exopolysaccharides Induced by Ceftriaxone Regulated Human Gut Microbiota in vitro - Li, Baiyuan; Chen, Huahai; Cao, Linyan; Hu, Yunfei; Chen, Dan; Yin, Yeshi (Frontiers in Microbiology, 2021)
A stable intestinal microflora is an essential prerequisite for human health. This study investigated the interaction between Escherichia coli exopolysaccharides (named EPS-m2) and the human gut microbiota in vitro. The EPS-m2 was produced by E. coli WM3064 when treated with ceftriaxone. The monosaccharide composition analysis revealed that EPS-m2 is composed of glucuronic acid, glucose, fucose, galactose/N-acetyl glucosamine, arabinose, xylose, and ribose with a molar ratio of approximately 77:44:29:28:2:1:1. The carbohydrates, protein, and uronic acids contents in EPS-m2 was 78.6 ± 0.1%, 4.38 ± 0.11%, and 3.86 ± 0.09%, respectively. In vitro batch fermentation experiments showed that 77% of EPS-m2 could be degraded by human fecal microbiota after 72 h of fermentation. In reverse, 16S rRNA gene sequencing analysis showed that EPS-m2 increased the abundance of Alistipes, Acinetobacter, Alloprevotella, Howardella and Oxalobacter; GC detection illustrated that EPS-m2 enhanced the production of SCFAs. These findings indicated that EPS-m2 supplementation could regulate the human gut microbiota and might facilitate modulation of human health.